The Government's Responsibility in Enforcing The Law on Plastic Pollution in The Sea - Lusy Erawati (Green Publisher Indonesia, 2024)
The proliferation of plastic pollution in the sea has emerged as a critical global issue, posing severe threats to marine ecosystems and human health. This study delves into the government's responsibility in addressing plastic waste pollution in Indonesian waters, where plastic waste has become a significant environmental concern. Despite existing regulations, the enforcement of laws related to plastic waste pollution remains inadequate, with various challenges hindering effective implementation. By employing a juridical-normative approach, this research analyzes the government's role in preventing environmental pollution and enforcing laws pertaining to plastic waste pollution in the sea. Key findings highlight the necessity for specific regulations targeting plastic waste management and the importance of enhancing law enforcement mechanisms. Recommendations include strengthening preventive measures, such as awareness campaigns and administrative sanctions, to foster responsible plastic waste management practices.